Increased intra-subject variability in reward behavior relates to symptom severity in schizophrenia - I-Fei Chen; Yu-Chen Chan; Chih-Min Liu; Yi-Ting Lin; Ming H. Hsieh; Tzung-Jeng Hwang; Tai-Li Chou; Chen-Chung Liu; Yi-Ling Chien; Georg Northoff (Schizophrenia)
Abstract Schizophrenia (SZ) is a complex disorder characterized by positive and negative symptoms that have been linked to dysfunction in cognition and reward motivation. Recent findings show higher inter-subject variability in SZ in various cognitive functions. This raises the question of whether there is also higher intra-subject variability in SZ at the psychological level, specifically increased variability across the trials of a psychological task within the subject itself, that is, intra-subject variability. To examine fluctuations in behavior during a reward-based discrimination and liking task, we analyzed intra-subject variability in SZ and observed the following: (i) increased intra-subjective variability across all four behavioral measures, that is, response times (RT) for discrimination and liking tasks, as well as accuracy (ACC) and liking ratings; (ii) significant correlation of the different measures’ intra-subject variabilities across the distinct tasks, e.g., RT, ACC, and liking ratings among each other; and (iii) relation of the increased intra-subjective variability in the behavioral measures (RT, ACC, liking) with overall and general psychopathological symptom severity, as measured by the positive and negative syndrome scale (PANSS). Together, we demonstrate abnormally increased intra-subjective variability in a reward-motivation task in SZ and its key role in relation to symptom severity. This increased intra-subject variability at the psychological-behavioral level suggests abnormal and imprecise timing in cognitive processing, which aligns with analogous findings of temporal imprecision at the neural level.